The lived class and racialization - histories of 'foreign workers' children's' school experiences in Denmark - Jin Hui Li (Taylor & Francis Group, 2021)
In recent years, the Danish education context has seen an increased concern about underperforming students with migratory histories (particularly students perceived as non-Western descendants) in the political and pedagogical discourses. There seem to be some historical tensions between the societal expectation of class mobility through education on one hand and the neglect of issues of class in the curriculum of schooling for migrant students on the other. These groups of students were labelled 'foreign workers' children' in the 1970s' education policy, with stress on 'the foreign' rather than 'the worker' part. Based on oral history interviews with former migrant students, this article explores how the class process for migrant students operated through racialized practices in Danish schooling in the 1980s. Contributing to the literature on migrant education and class experiences, the study finds that the migrant students' lived class experiences are woven into the processes of racialization in such a way that even the migrant students from academic homes had racialized struggles sustaining their middle-classed positionality in the Danish school. The arrangement of the power structures of class is hence strongly interwoven with the power structure of race in the historical context of Danish schooling.